Evaluation of enteric methane emission from dairy and beef fattening production in Japan - HIROOKA, Hiroyuki (Journal of the Japanese Agricultural Systems Society, 2023)
It is well known that cattle is a large contributor to environmental impacts, especially enteric methane emissions. In this study, the impacts of enteric methane emissions from dairy and beef production (Japanese Black fattening) in Japan were analyzed based on the two metrics; (i) expressed as CO2-equivalents (CO2e) using 100 year Global Warming Potential (GWP100) and (ii) CO2 warming equivalent (CO2we) derived from GWP* which considers additional warming as a function of the time line of short lived methane emission. The later metric can be used to guide climate action aligned with temperature-based climate stabilization goals. Data of historical enteric methane emissions from dairy and beef cattle from 1990 to 2020 were used and the future methane emissions till 2050 were predicted based on the data by assuming than milk and beef production were maintained at the level in 2020. Two alternative scenarios (1% and 2% reductions per year of enteric methane emissions) were also evaluated in addition to the base scenario (no reduction). The continues reduction of enteric methane emission for commonly used metric (CO2e) from dairy production was resulted from decreasing animal numbers. The negative values for enteric methane emission by CO2we were obtained all over the years (including the future predictions) despite positive CO2e, this being because CO2we is related with the level of 20 years ago. In contrast, enteric methane emissions from beef cattle production were relatively stable compared with dairy cattle production. It was suggested that Japanese beef production would approach climate neutrality in the future if enteric methane emission can be reduced by more than 1% per year.